Chemotherapy Toxicity in BRCA Mutation Carriers Undergoing First‐Line Platinum‐Based Chemotherapy. (25th July 2019) - Weitzner, Omar; Yagur, Yael; Kadan, Yfat; Beiner, Mario E.; Fishman, Ami; Ben Ezry, Emilie; Amitai Komem, Daphna; Helpman, Limor
Abstract: Objective: BRCA mutations are the most frequent mutations causing homologous recombination defects in epithelial ovarian cancers (EOC). Germline mutation carriers are heterozygous for the mutation and harbor one defective allele in all cells. This has been hypothesized to cause increased susceptibility to DNA damage in healthy cells as well as neoplastic ones. Our objective was to assess chemotherapy‐associated toxicities in patients with epithelial ovarian cancer with and without a germline BRCA mutation. Mateials and Methods: A retrospective cohort study of patients with EOC receiving first‐line platinum‐based chemotherapy at a single center between 2006 and 2016. Indices of chemotoxicity, including blood counts, transfusion requirements, granulocyte colony‐stimulating factor (gCSF) prescriptions, episodes of febrile neutropenia, and treatment delays were compared for BRCA mutation carriers and noncarriers. Results: A total of 90 women met the inclusion criteria, including 31 BRCA mutation carriers (34%) and 59 noncarriers (66%). Mean hemoglobin, neutrophil count, and platelet counts during treatment were comparable for the two patient groups. There was a trend toward a higher frequency of hematological events in BRCA mutation carriers (neutropenia <1500 per mL: 6% vs. 0%, p = .12; thrombocytopenia <100, 000 per mL: 23% vs. 9%, p = .07), but these differences were not statistically significant. Similarly, no significant differences were found in surrogates of bone marrow toxicity such as blood transfusions, use of gCSF, episodes of febrile neutropenia, or treatment delays. Conclusion: BRCA mutation carriers and noncarriers receiving first‐line platinum‐based chemotherapy for EOC have similar hematologic toxicity profiles. Clinicians treating these patients can be reassured that chemotherapy dosing or schedule do not require adjustment in patients carrying BRCA mutations. Implications for Practice: Patients with ovarian cancer carrying BRCA mutations are more likely to have serous tumors and present with higher CA125 levels. Germline BRCA mutation status is not associated with increased frequency of adverse hematologic events among patients with ovarian cancer being treated with first‐line platinum‐based chemotherapy. Germline BRCA mutations are also not associated with more treatment delays or a lower number of courses completed in this patient population. These findings should reassure practitioners engaged in care for patients with ovarian cancer that BRCA mutation status most likely will not affect chemotherapy dosing or schedule. Abstract : In light of the sparsity of clinical data on chemotherapy toxicity in BRCA mutation carriers, a single institution retrospective cohort study was undertaken to explore differences in chemotherapy‐associated toxicities between epithelial ovarian cancer patients carrying a germline BRCA mutation and patients who do not harbor such a mutation. The results are described here.